2022
DOI: 10.1002/ejhf.2596
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical trial of cell therapy in heart failure with preserved ejection fraction

Abstract: We investigated the effects of CD34 + cell therapy in patients with heart failure with preserved ejection fraction (HFpEF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…CD34+ cell therapy was associated with improvements in E/e' (primary endpoint), N-terminal pro-B-type natriuretic peptide, exercise capacity, and local myocardial strain at the cell injection sites, compared with pre-implantation values. 27…”
Section: Novel Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD34+ cell therapy was associated with improvements in E/e' (primary endpoint), N-terminal pro-B-type natriuretic peptide, exercise capacity, and local myocardial strain at the cell injection sites, compared with pre-implantation values. 27…”
Section: Novel Optionsmentioning
confidence: 99%
“…The effects of CD34+ transendocardial cell therapy have been assessed in a prospective non‐randomized pilot study enrolling 30 HFpEF patients who underwent cell transplantation and were followed for 6 months. CD34+ cell therapy was associated with improvements in E/e' (primary endpoint), N‐terminal pro‐B‐type natriuretic peptide, exercise capacity, and local myocardial strain at the cell injection sites, compared with pre‐implantation values 27 …”
Section: Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%
“…They then received therapy with CD34+ cells administered transendocardially in a second phase. After a follow-up period of 6 months, they found that CD34+ cell transplantation is feasible and safe and was associated with favorable results based on the measurement of E/e' ratio, NT-proBNP levels, and the distance walked in the 6 min walk test (6 MWT) [162].…”
Section: Cell Therapy and The Futurementioning
confidence: 99%